2015
DOI: 10.5993/ajhb.39.4.8
|View full text |Cite
|
Sign up to set email alerts
|

Little Cigar and Cigarillo Beliefs and Behaviors among African-American Young Adults

Abstract: Future research should assess LCC intended versus altered use and create culturally relevant intervention measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 0 publications
3
21
0
Order By: Relevance
“…This is consistent with recent findings from Sterling et al 16 and Stephens et al 15 who conducted focus groups with users of little cigars and cigarillos, and concluded that flavored little cigars and cigarillos are primarily used as a vehicle to smoke marijuana. In the present study, we found users have specific terms for cigars used for smoking marijuana, consistent with research showing that many blunt users do not necessarily recognize themselves as cigar users.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is consistent with recent findings from Sterling et al 16 and Stephens et al 15 who conducted focus groups with users of little cigars and cigarillos, and concluded that flavored little cigars and cigarillos are primarily used as a vehicle to smoke marijuana. In the present study, we found users have specific terms for cigars used for smoking marijuana, consistent with research showing that many blunt users do not necessarily recognize themselves as cigar users.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings were consistent with focus group data gathered by Yerger et al, 8 who found that African American youth considered only large/traditional cigars to be “cigars,” whereas other types of cigar products were referred to by brand names. We also found that very few users could identify the little cigar as a “cigar,” which is consistent with evidence from focus groups with young adult African-American little cigar or cigarillo users, who found that the term “little cigar” was confusing and “weird.” 15 Together, these findings add to the growing body of evidence that the language con- sumers use to identify and differentiate cigar subtypes is extremely varied; and in the case of little cigars, consumers may not even identify these products as cigars.…”
Section: Discussionmentioning
confidence: 83%
“…Consistent with other literature, this finding may indicate that Black youth consider CCLCs, including modified CCLCs, a healthier alternative for nicotine consumption. 11,34,35 This perception may be perpetuated by the abundance of cigar product advertising by tobacco companies pervasive in low-income communities…”
Section: Limitationsmentioning
confidence: 99%
“…Research on Black men and health behaviors has mainly focused on what health behaviors they engage in, their beliefs, and how these behaviors impact their overall health outcomes, not the factors that impact their engagement in these health behaviors. 3,7,34-36 Because health behaviors are influenced by many factors, it is important to understand what elements outside of the individual’s knowledge and beliefs impact the behavior they engage in. It is recognized that findings from this study may not be applicable to all Black men, but it is believed that these findings further Black men’s health research by researching what impacts health behaviors in younger groups of Black men.…”
Section: Commentmentioning
confidence: 99%